Before the Age of Prejudice A Muslim Woman's National Security Work with Three American Presidents - A Memoir - Tahir-Kheli, Shirin (Springer Singapore, 2018)
"From India to Pakistan to the United States, Shirin Tahir-Kheli has lived a remarkable life, rising to become one of the highest ranking Muslim-Americans in U.S. diplomatic history. Working alongside her after 9/11, I witnessed Shirin's dedication firsthand. In this evocative memoir she recounts her extraordinary journey, reflecting on faith, family, and the country she so ably served." -Condoleezza Rice, former Secretary of State, former National Security Advisor "As a woman, a Muslim, and a native of India and Pakistan with a long and distinguished career in American foreign policy, Shirin Tahir-Kheli's life has been full of extraordinary breakthroughs. In her forthright, illuminating, and fascinating memoir, she provides insights on working for three presidential administrations on American foreign policy and national security, as well as on promoting peace in south Asia. As a diplomat, political insider, and scholar, Ambassador Tahir-Kheli has witnessed changes in U.S. diplomacy over several decades and from varying perspectives. Indeed, her career is remarkable and one-of-a-kind. This is a must-read for anyone interested in South Asia and national policymaking." -Vartan Gregorian, President, Carnegie Corporation of New York This book offers a fascinating insider's perspective from one who happens to be a Muslim woman on U.S. foreign policy making during three Republican presidential administrations. Shirin Tahir-Kheli's life story is a testament to the promise and delivery of the American dream in another era and is a must read for scholars and policy makers. Shirin Tahir-Kheli is Senior Fellow at the Foreign Policy Institute at Johns Hopkins University School of Advanced International Studies. As Senior Adviser to the Secretary of State, Tahir-Kheli played a key role in policy formulation toward UN Reform during a critical year for reform efforts and has been central to the effort to support the Empowerment of Women. She served in various senior positions including as Special Assistant to the President and Senior Advisor at the White House National Security Council.